Imposing Phase II and Phase III Clinical Trials of Targeted Drugs for Glioblastoma: Current Status and Progress - Wang, Yaning; Chen, Wanqi; Shi, Yixin; Yan, Chengrui; Kong, Ziren; Wang, Yuekun; Wang, Yu; Ma, Wenbin (Frontiers in Oncology, 2021)
The most common primary intracranial tumor is glioma, among which glioblastoma (GBM) has the worst prognosis. Because of the high degree of malignancy of GBM and frequent recurrence after surgery, postoperative therapy, including chemotherapy, radiotherapy, targeted therapy, and immunotherapy, is particularly important. A wide variety of targeted drugs have undergone phase III clinical trials for patients with GBM, but these drugs do not work for all patients, and few patients in these trials have prolonged overall survival. In this review, some imposing phase III clinical trials of targeted drugs for glioma are introduced, and some prospective phase II clinical trials that have been completed or are in progress are summarized. In addition, the mechanisms of these drugs are briefly introduced, and deficiencies of these clinical trials are analyzed. This review aims to provide a comprehensive overview of current research on targeted drugs for glioma to clarify future research directions.